Akselerasi Birokrasi Digital: Dampak Digitalisasi dan Motivasi Kerja terhadap Produktivitas Pegawai di Lingkungan Kemnaker RI: Accelerating Digital Bureaucracy: The Impact of Digitalization and Work Motivation on Employee Productivity within the Indonesian Ministry of Manpower - Mutiara Cantika Oktarina (PT Cakrawarti Empat Proksi, 2026)
The development of digital technology encourages government agencies to improve performance through a more efficient and adaptive work system. The Directorate of Work Introduction of the Ministry of Manpower of the Republic of Indonesia is required to implement digitalization and strengthen employee work motivation to increase productivity. This study aims to determine the effect of work system digitization and work motivation on employee productivity. The research was conducted with a quantitative approach through distributing questionnaires to 40 respondents and analyzed using multiple linear regression with the help of SPSS version 26. Partial test results show that work system digitization (sig 0.000; t-count 32.239 > t-table 2.026) and work motivation (significance value 0.000; t-count 4.539 > 2.026) have a positive and significant influence on employee productivity. Simultaneously, both variables also have a significant effect with an F-count value of 58.990 > F-table 3.24 and R² of 0.996, which means 99.6% of the variation in productivity is explained by the two variables. The results of this study indicate that improving work technology and employee motivation needs to be a concern in an effort to improve employee performance.Digitalization Of Work Systems, Work Motivation, Employee Productivity